Value addition to rice bran oil as toilet soap: Wijayaratne T. D.1, Munasinghe M.1 and Wijayasiriwardana T. D. C. M. K. 2* (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2023)
The oil extracted from rice bran is underutilized in Sri Lanka. It is a rich source of essential fatty acid linoleic acid. Linoleic acid is most favored in the production of cosmetic products for its emollient and moisturizing properties. The aims of this study were to extract rice bran oil from red, mixed and parboiled rice bran, prepare a composite crude rice bran oil sample, analyze crude composite oil for physicochemical characteristics stated in Sri Lanka Standard 1592: 2018, formulate rice bran oil enriched toilet soap and evaluate its compliance with the specifications mentioned in Sri Lanka Standard 34: 2009. Rice bran oil was extracted using hexane and composite crude rice bran oil was analyzed by methods mentioned in Sri Lanka Standard 313. Three trials were carried out for the formulation of a toilet soap by hot saponification reaction and methods in the International Organization for Standardization were followed to determine the characteristic requirements for the toilet soap. The highest oil yield (8.0%) was given by parboiled rice bran and composite rice bran oil showed 0.911 relative density, 1.456 refractive index, 103.122 g/100g of oil iodine value, 196.626 saponification value, 0.08% moisture and volatile matter, 16.0% free fatty acids and 30.0 meq/ Kg peroxide value. Trial 3 formulated soap showed 78.23 % total fatty matter, 1.8% matter insoluble in ethanol, 0.05% free caustic alkali and 0.2% total free alkali therefore complying with the requirements for a toilet soap.